2016
DOI: 10.1063/1.4939913
|View full text |Cite
|
Sign up to set email alerts
|

An accurate locally active memristor model for S-type negative differential resistance in NbOx

Abstract: A number of important commercial applications would benefit from the introduction of easily manufactured devices that exhibit current-controlled, or “S-type,” negative differential resistance (NDR). A leading example is emerging non-volatile memory based on crossbar array architectures. Due to the inherently linear current vs. voltage characteristics of candidate non-volatile memristor memory elements, individual memory cells in these crossbar arrays can be addressed only if a highly non-linear circuit element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(131 citation statements)
references
References 46 publications
4
127
0
Order By: Relevance
“…The model parameters for the CC-NDR simulation are chosen as: serial resistor R s = 3.3 kΩ, memory LRS R M,LRS = 4 kΩ, length of the threshold regime l Th = 5 nm, and T amb = 293.15 K. The simulated I-V D , I-V app , and I-V Th curves are shown in Figure 8 a. In addition to the results of previous studies, [ 10,11 ] we simulate a full S-type NDR curve for the case of the I-V D characteristic including the negative slope after the turn-on point, which gradually changes into a positive slope at higher currents. [ 7,11,32 ] The origin of the continuous NDR behavior is the transition to a continuous temperature increase in the NbO 2 regime with increasing applied voltage as shown in the T Th versus V app plot in Figure 8 b.…”
Section: Current Controlled Negative Differential Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The model parameters for the CC-NDR simulation are chosen as: serial resistor R s = 3.3 kΩ, memory LRS R M,LRS = 4 kΩ, length of the threshold regime l Th = 5 nm, and T amb = 293.15 K. The simulated I-V D , I-V app , and I-V Th curves are shown in Figure 8 a. In addition to the results of previous studies, [ 10,11 ] we simulate a full S-type NDR curve for the case of the I-V D characteristic including the negative slope after the turn-on point, which gradually changes into a positive slope at higher currents. [ 7,11,32 ] The origin of the continuous NDR behavior is the transition to a continuous temperature increase in the NbO 2 regime with increasing applied voltage as shown in the T Th versus V app plot in Figure 8 b.…”
Section: Current Controlled Negative Differential Resistancementioning
confidence: 99%
“…It might even be increased by stacking multiple layers of passive matrices to a 3D structure. [7][8][9][10][11][12][13][14][15][16][17][18] Threshold devices show an abrupt resistance change at a certain voltage stress V Th,ON . [ 1,4 ] This serious issue is alleviated by either complementary resistive switching devices or by the integration of a selector device in addition to the passive ReRAM, so called "1S1R" structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some material systems, such as VO 2 or NbO 2 , this process leads to an observed negative differential resistance (NDR), generating a strong but volatile change in the conductance. In fact, many forms of NDR can be ultimately described as a positive feedback-driven effect based on internal temperature coupled to the electronic transport 73,74 . Consequently, owing to the inherent positive feedback, only a small amount of input signal is needed to generate a large effect, thus supplying the needed neuronal amplification alluded to earlier.…”
Section: The Role Of Chemistry and Biological Detailsmentioning
confidence: 99%
“…Examples of conventional two-terminal thin-film based selectors include Schottky diodes [17] , tunneling junctions [18,19] , ovonic threshold switches (OTS) [20][21][22][23] and metal-insulator transitions (MIT) [24][25][26][27][28] . Kim et al has demonstrated 32×32 crossbar array composed of a stacked Schottky diode and a unipolar memristor.…”
Section: Introductionmentioning
confidence: 99%